Wandering the Wards An Ethnography of Hospital Care and its Consequences for People Living with Dementia - Featherstone, Katie (Routledge Studies in Health and Medical Anthropology, 2021)
"Wandering the Wards provides a detailed and unflinching ethnographic examination of life within the contemporary hospital. It reveals the institutional and ward cultures that inform the organisation and delivery of everyday care for one of the largest populations within them: people living with dementia who require urgent unscheduled hospital care. Drawing on five years of research embedded in acute wards in the UK, the authors follow people living with dementia through their admission, shadowing hospital staff as they interact with them during and across shifts. In a major contribution to the tradition of hospital ethnography, this book provides a valuable analysis of the organisation and delivery of routine care and everyday interactions at the bedside, which reveal the powerful continuities and durability of ward cultures of care and their impacts on people living with dementia."